Transfer of beef bacterial communities onto food-contact surfaces - Guron, Giselle K. P.; Cassidy, Jennifer M.; Chen, Chin-Yi; Paoli, George C. (Frontiers in Microbiology, 2024)
Introduction Food spoilage and pathogenic bacteria on food-contact surfaces, especially biofilm-forming strains, can transfer to meats during processing. The objectives of this study were to survey the bacterial communities of beef cuts that transfer onto two commonly used food-contact surfaces, stainless steel (SS) and high-density polyethylene (HDPE) and identify potentially biofilm-forming strains. Methods Top round, flank, chuck, and ground beef were purchased from 3 retail stores. SS and HDPE coupons (approximately 2cm × 5cm) were placed on beef portions (3h, 10°C), after which, the coupons were submerged halfway in PBS (24h, 10°C). Bacteria from the beef cuts and coupon surfaces (n = 3) were collected, plated on tryptic soy agar plates and incubated (5 days, 25°C). Bacterial isolates were identified by 16S rRNA gene amplicon sequencing and assayed for biofilm formation using a crystal violet binding (CV) assay (72h, 10°C). Additionally, beef and coupon samples were collected for bacterial community analysis by 16S rRNA gene amplicon sequencing. Results and discussion Sixty-one of 972 beef isolates, 29 of 204 HDPE isolates, and 30 of 211 SS isolates were strong biofilm-formers (Absorbance>1.000 at 590 nm in the CV assay). Strong-binding isolates identified were of the genera Pseudomonas, Acinetobacter, Psychrobacter, Carnobacterium, and Brochothrix. Coupon bacterial communities among stores and cuts were distinct (p < 0.001, PERMANOVA), but there was no distinction between the communities found on HDPE or SS coupons (p > 0.050, PERMANOVA). The bacterial communities identified on the coupons may help determine the communities capable of transferring and colonizing onto surfaces, which can subsequently cross-contaminate foods.